The Effect Of Organizational Citizenship Behavior (OCB) And Organizational Commitment On Employee Performance Of PT. Bukit Angkasa Makmur Central Bengkulu - Sherli Carolin; Khairul Bahrun (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2024)
The title of this study is the effect of organizational citizenship behavior (OCB) and organizational commitment on the performance of employees of PT. Bukit Angkasa Makmur Central Bengkulu. This research is based on the importance of employee performance in an organization. Employee performance is influenced by several factors, including organizational citizenship behavior and organizational commitment. This study aims to analyze the effect of organizational citizenship behavior and organizational commitment on the performance of employees of PT. Bukit Angkasa Makmur Bengkulu.This type of research is quantitative research with a descriptive approach. The population of this study were all employees of PT. Bukit Angkasa Makmur Bengkulu. The number of research samples was 175 people. Data collection was carried out using a questionnaire. Data analysis techniques using multiple linear regression analysis techniques.The results of data analysis obtained multiple linear regression equations as follows: Y = 1.083 + 0.513 X1 + 0.696 X2. The results of the analysis show that organizational citizenship behavior has a positive and significant effect on employee performance (tcount = 7.239 and Sig. = 0.000) and organizational commitment has a positive and significant effect on employee performance (tcount = 6.808 and Sig. = 0.000). Simultaneously organizational citizenship behavior and organizational commitment to employee performance (Fhitung = 175,649 and Sig. = 0.000).It is recommended to the management of PT. Bukit Angkasa Makmur Bengkulu to be able to improve employee performance by increasing organizational citizenship behavior and employee organizational commitment.